Neurocognitive recovery and global cerebral perfusion improvement after cranioplasty in chronic sinking skin flap syndrome of 18 years: Case report using arterial spin labelling magnetic resonance perfusion imaging. (July 2020) - Woo, Peter Yat Ming; Mak, Calvin Hoi Kwan; Mak, Henry Ka Fung; Tsang, Anderson Chun On
Highlights: Cranioplasty may provide neurocognitive improvement in patients with sinking skin flap syndrome. The advantages of pCASL MR perfusion in assessing CBF before and after cranioplasty is illustrated. Imaging may be useful for selecting patients that would benefit most from early cranioplasty and for assessments for prospective trials. Abstract: Sinking skin flap syndrome (SSFS) is a complication among long-term survivors of stroke or traumatic brain injury treated by decompressive craniectomy. The syndrome encompasses a wide spectrum of neurological symptoms including cognitive decline, seizures, speech and sensorimotor deficits. Early cranioplasty appears to improve cerebral perfusion, but the efficacy of cranioplasty in neurocognitive outcome in long-standing SSFS patient is unclear. We report a 64-year-old patient who suffered from traumatic brain injury and underwent decompressive craniectomy 18 years ago. She had chronic SSFS with pre-cranioplasty assessments demonstrating severe neurocognitive impairments which were static over time. After cranioplasty with custom-made polyetheretherketone flap to restore the 264 cm 2 skull defect, magnetic resonance perfusion scan with pseudo-continuous arterial spin labelling technique showed a two-fold augmentation of cerebral blood flow in both frontal lobes, as well as areas distal to the sunken skin flap compared to baseline. This is accompanied by improvement of neurocognitive function as assessed by Montreal Cognitive Assessment, Neurobehavioral Cognitive State Examination, and Rivermead Behavioural Memory Test three and six months after cranioplasty. The patient's quality of life and that of her primary carer also showed improvement. This report describes a case of neurocognitive and global cerebral perfusion improvement after cranioplasty in the setting of prolonged SFSS of 18 years, and adds to the growing body of literature supporting the therapeutic role of cranioplasty beyond purely protective or cosmetic indications. The advantages and clinical utility of pCASL MR perfusion in assessing serial CBF before and after cranioplasty is illustrated.